Obtenção de complexos antimicrobianos zeólita-prata e sua aplicação em curativos biodegradáveis - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2023)
Exudative lesions proceed an infection in the wound and to occur the healing process wound dressings must be applied to absorb excess fluid from the lesion and have antimicrobial characteristics. Silver ions are widely used antimicrobials in these cases, but they present some difficulties related to the mode of release at the wound site. An alternative to controlling the release of Ag+ ions is to incorporate them into a controlled release system, such as zeolites, which are microporous minerals with ion exchange capacity and can be used as drug carriers. Therefore, this work witnessed the development of dressings based on cassava starch and malt bagasse with the addition of an antimicrobial developed from zeolite impregnated with silver ions. The zeolites were impregnated with 2000, 3000 and 4000 mg/L of AgNO3- in different conditions of pH (3, 4 and 5) and temperature (T) (25, 35 and 45 oC), obtaining 11 samples of the zeolite complex +silver (ZeAg) through a 23 factorial design. The eleven ZeAg complexes were characterized by particle diameter, scanning electron microscopy (MEV-FEG), infrared spectroscopy (FTIR), X-ray diffraction (XRD), ultraviolet-visible spectroscopy (UV-VIS) and action antimicrobial. After the tests, the most promising formulation was selected to be added to the 4 formulations of biodegradable dressings based on starch and malt bagasse, with ZeAg concentrations of 0, 0.5, 1 and 2% (w/v). Regarding the ZeAg complex, formulation 8 (AgNO3- at 4000 mg/L, pH 5 and T 45 oC) showed the best results in all analyzes performed, being the most promising formulation for presenting antimicrobial activity in the microbiological test, and also maintained an original crystalline structure of the zeolite after the experimental conditions used. The biodegradable dressings obtained by thermopressing were characterized in terms of thickness, density, solubility, water vapor permeability (PVA), water solubility and absorption index (ISA and IAA) and scanning electron microscopy (MEV-FEG). The dressings had a rough appearance and brownish colors due to the addition of malt bagasse, except for the control sample that presented whitish colors due to starch being the major component in this sample. There was no significant difference between the 4 ascending formulations in the thickness, density, solubility, water vapor permeability and ISA tests, in order to conclude that the addition of different concentrations of ZeAg8 complex and malt bagasse did not change the related properties of the dressings produced. Regarding the AAI, the sample with the addition of 0.5% obtained higher values in this parameter compared to the others. This difference may be the result of the high amount of pores that this sample presented, as observed in the scanning electron microscopy images, where these pores increase the contact surface with the water in the medium and provide greater absorption of water into the dressing. Regarding the mechanical properties of the materials, the formulations experienced a significant increase in hardness and tensile strength were those with the highest concentrations of the ZeAg complex, leading to the mechanical reinforcement of the dressings. Based on these results, it is necessary perform more analysis related to microbiological action wound dressings impregnated with ZeAg antimicrobial complex and also cytotoxicity action.
Keywords: zeólita; íons prata; amido; bagaço de malte; antimicrobiano; zeolite; silver ions; starch; malt bagasse; antimicrobial; CNPQ::CIENCIAS DA SAUDE::FARMACIA